THE BRAZILIAN LEGAL SYSTEM AND THE INTERNATIONAL ENVIRONMENTAL PRINCIPLES: AN APPROACH TO INSTRUMENTS FOR PROMOTING ENVIRONMENTAL SUSTAINABILITY AND THE PRECAUTIONARY PRINCIPLE - Humberto Gomes de Oliveira, José; Ferreira Júnior, José (Revista Gênero e Interdisciplinaridade, 2024)
This article aims to analyze the environmental principles established in the international order and recognized by the Brazilian legal system, in particular the 1988 constitutional text, with the aim of evaluating the effects of international legislation with regard to environmental matters, based on verification of a staggered and more accentuated regulatory development in the environmental field. The aim was to define the parameters of the new world economic order and the importance attributed to the outstanding principles of precaution, sustainable development and prevention, with a view to consolidating a relevant tool for promoting environmental protection. In this sense, by synthesizing a study on the adoption and adequacy of the principle elements of the international environmental order, an investigative aspect is created to promote awareness of the primacy of an environment that receives collective care both at a global and national level. The strengthening of international environmental law was also a concern of this article, even though it was a brief analysis, so that it shows the exact notion that the issue must involve all social actors, from individuals and even the most complex state structure, with the goal of defining and applying a normative framework on environmental issues, in the international sphere and its applicability in national territory, through the due process of internalization of treaties and, in particular, the economic order in the 1988 Constitution, facing the challenges arising from growth world population and the urgent need to confront the catastrophic effects of the process of industrialization and large-scale consumption, considering environmental sustainability.